PENDEKATAN EFEKTIF DALAM MENENTUKAN HARGA JUAL MELALUI PERHITUNGAN HARGA POKOK PRODUKSI PADA USAHA GORONG-GORONG BAPAK SARIFUDIN - Sri Wahyuni; Tuti Fitriani; Hizkia Rikcanto (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2025)
This research aims to explore an effective approach in determining selling prices in Mr. Sarifudin's main business, which previously faced problems in the classification of production costs and inaccurate setting of selling prices. The method used is a descriptive method, this study focuses on the calculation of the cost of production (COG) and selling price, with quantitative data that includes raw material costs, labor, and factory overhead, which are collected through observation, interviews, and documentation. The results of this analysis show that the total cost of production for 2023 is IDR 190,771,360, - or IDR 104,877, - per unit. Furthermore, the ideal selling price with the cost plus pricing method is IDR 174,877 per production unit plus a margin of IDR 70,000,-, which is higher and more realistic than the company's initial selling price.